The Effect of Ultraviolet Radiation on Human Health - Ahmed Mohammed Abbas Ibrahim; DOAA OMAR CHYAD KHALIL; Yasmin ali Mohammed Hussein Neamah; Ameer Ali Abdul Baqi Hassan; Amenah hamld khudhalr Salman (Genius Journals, 2024)
UV radiation has both detrimental effects and medical applications. Overexposure to UV radiation can cause sunburns, premature skin aging, and increase the risk of skin cancer. It can also damage the eyes and weaken the immune system, potentially leading to genetic disorders and various cancers. However, controlled exposure to specific UV wavelengths is used in phototherapy to treat skin disorders like psoriasis, vitiligo, and atopic dermatitis. UV light reduces inflammation and modulates immune responses. UVB radiation enables the synthesis of vitamin D, essential for bone health and immune function. Additionally, UVC radiation has germicidal properties and is used for disinfection in healthcare settings to reduce the risk of infections. To ensure safety, sun protection measures like sunscreen and protective clothing should be followed. In medical settings, UV radiation should be carefully monitored and controlled, and protective measures like UV-blocking goggles and clothing should be used. Regular skin surveillance is important for detecting UV-induced damage. By implementing these measures, the negative effects of UV radiation can be minimized while maximizing its medical benefits
Keywords: UV radiation; skin surveillance; Human Healt